HUBUNGAN KODE ETIK PUSTAKAWAN DENGAN KINERJA PUSTAKAWAN DI BADAN PERPUSTAKAAN, ARSIP DAN DOKUMENTASI PROVINSI SULAWESI UTARA - GOLUNG, ANTHONIUS MOSES (Sam Ratulangi University, 2015)
ABSTRACT : The purpose of librarianâ€™s ethic of conduct is to keep the prestige and moral well,and the librarianâ€™s moral increases the service to society and profession quality.Therefore the librarianâ€™s in doing their professional duty must pay attention and apply it asit must be based on aptitude and behaviourâ€™s norm and politeness as a librarianâ€™s ethic of condutct.This study is to know the relation betwewn ethic of conduct and librarianâ€™s ethic ofproduct, documentation and archives of North Sulawesi.This study covers the 32 respondents. Those are all the librarians.The result of the studyshows that the relation between ethic of conduct of the librarians with their performance in libraryboard, archives and documentation of North Sulawesi province have strong relation or significant.This case is shown by â€œt testâ€ which the mark of â€œT testâ€ is 73 bigger then the mark of â€œTtableâ€ that is 2,042 and it is seen more cleary with the mark â€œr testâ€ which is the same as 0,7 that isconsultated on the guillford table, it shows strong relation (significant).Furthermore, based on the result of co-efficient determination or determiner powerlibrarianâ€™s ethic of conduct and their performance in libraryâ€™s board, archives and documentation ofNorth Sulawesi is 0,49, so it can be concluded. The influence of librarianâ€™s ethic of conduct towardlibrarianâ€™s performance in libraryâ€™s board, archives and documentation of North Sulawesi provinceis 49%. And the rest is 51% is influenced of variable which is not observed in this study.Keyword : librarianâ€™s ethic of conduct